Where and When is the Next Pandemic Coming From? Viral Ancestry may Provide Clues - Cock, Ian E (Pharmacognosy Communications)
In the aftermath of the height of the SARS-CoV-2 viral pandemic that resulted in considerable mortality and brought the world to a standstill for several years, epidemiologists and virologists are concerned about the next pandemic. Whilst the effects of COVID-19 are still being felt globally (especially by those experiencing ‘long COVID’) the focus of many researchers and clinicians has now turned to predicting when and where the next pandemic will arise. Prevention and/or preparedness allow for proactive protective measures to be taken, rather than requiring the medical community to react as new pathogens arise and take hold in society. It is likely that a proactive approach may save many lives. Key to this is the ability to predict when new pathogens will emerge and instigate new pandemics. A recent study explores how viral family history has the potential to assist scientists to identify problematic viral strains, and to therefore predict the next pandemic.1 The authors of that study traced the lineage and evolution of 743 distinct RNA viruses and identified 79 viral lineages that pose the greatest risk to human health. This research may aid researchers and viral monitoring programs to prioritise which viruses require the greatest vigilance. This may also may allow global authorities to prepare for future pandemics by guiding the development of diagnostic tools and vaccines, which could potentially save substantial loss of life.